Kendali Pergerakan Sumbu Pitch Sistem Twin Rotor Multi Input Multi Output (TRMS) dengan Menggunakan Metode Pole Placement State Feedback - Ulya Darajat, Anisa; Istiqphara, Swadexi; Faida, Afida Nur (ELECTRON Jurnal Ilmiah Teknik Elektro, 2022)
Twin Rotor Multi Input Multi Output System (TRMS) is an aerial vehicle prototype which is used to test the control system in controlling the air vehicle. TRMS has characteristics similar to helicopters which are non-linear and multi-input multi-output (MIMO) systems. The design of the control system is a challenge for researchers with the aim of the vehicle being able to move according to the specified target, including the rotational movement that maintains the stability of the vehicle when navigating. Based on these problems, this paper will design a TRMS movement control system on the pitch axis. The method used in this research is the linear pole placement state feedback control system method which is obtained by placing the plant poles to the desired poles. The results obtained show that the pitch movement can be controlled without steady state error but there is an overshoot in the opposite direction to the target during the rise time, based on the three tests, the best settling time value is 0.46s with an overshoot rise time of 0.19rad.